Toll-like receptor 4 orchestrates neutrophil recruitment into airways during the first hours of Bordetella pertussis infection - Moreno, Griselda Noemí (2013)
Most of the knowledge on the impact of Bordetella pertussislipo-oligosaccharide (LOS) on the infectious process was obtained when the bacteria was established within the host. The aim of the present work was to determine the role of TLR4 at a very early step of the infectious process. To this end we used a transcriptomic approach on B. pertussis intranasal infection model in C3H/HeN, a TLR4-competent mouse strain, and C3H/HeJ, a TLR4-deficient mouse strain. The expression of approximately 140 genes was significantly changed 2 h post-infection in the C3H/HeN animals compared to the C3H/HeJ animals, which were essentially non-responders at this early time point. Pathways specific for immunity and defense, chemokine- and cytokine-mediated functions and TLR signaling, were activated upon infection in the TLR4 competent mice either at 2 h or 24 h. Furthermore, we observed that TLR4 signaling is absolutely required to promote the rapid recruitment of neutrophils into the airways. Interestingly, the depletion of those neutrophils impacted on B. pertussislung counts in the first three days, thereby exacerbating the lung infection. In summary, we determined that TLR4 is a central player in initial neutrophil recruitment and orchestration of the very early innate defense against B. pertussis.